The mostly true story of Jack - Barnhill, Kelly Regan (Little, Brown, 2011)
Jack is practically invisible at home, but when his parents send him to Hazelwood, Iowa, to spend a summer with his odd aunt and uncle, he suddenly makes friends, is beaten up by the town bully, and is plotted against by the richest man in town.